ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT INFLASI DAN KINERJA PEREKONOMIAN DI INDONESIA - Mulvita, Loly; Amar, Syamsul; Idris, Idris (Program Studi Magister Ilmu Ekonomi, 2014)
This study aims to analyze and determine (1) the influence of the economy, interest rates, money supply, government spending and wages on inflation in Indonesia, (2) the effects of inflation, government spending, taxes, and wages on the economy in Indonesia. Type of data is the documentary data, the data source is a secondary data as well as data in the form of time series from the first quarter of 2000 - the fourth quarter of 2012. This study uses a simultaneous equation model analysis tool with Two Stages Least Squared method (TSLS). Endogenous variables in the study was the economy and inflation. And exogenous variable is government spending, tax, interest rate, money supply and wage. The research concludes that (1) the Economy, interest rates, money supply, government spending and wage on inflation in Indonesia affected significantly. (2) inflation, government spending, taxes have a significant effect on the economy in Indonesia. However, the study does not affect wages in the economy significantly. Based on the results of the discussion, Governments and Bank Indonesia is expected to maintain the stability of prices and restrained inflation range in order to maintain macroeconomic stability Indonesia. The policies that can be suggested is Bank Indonesia needs to conduct monetary policy gradually and consistently setting interest rates in order to control the money supply and the inflation rate. Required effort or government policy makers to be able to continue to increase in Indonesia's economy by increasing government spending (Expansionary Fiscal Policy) which aimed at the improvement of development expenditure. Keywords: economy, inflation, government spending, tax, interest rate, money supply and wage.